Effect of Sn and Cu on corrosion resistance of lamgalmnconi type alloys - Casini, Julio Cesar Serafim (2017)
This paper reports the results of investigation carried out to evaluate the corrosion resistance of tin and copper in as-cast alloys represented by two sequential series, first: La0.7Mg0.3Al0.3Mn0.4Co0.5-xSnxNi3.8 (x = 0.0, 0.1, 0.2, 0.3 and 0.5) and second: La0.7Mg0.3Al0.3Mn0.4Sn0.5-yCuyNi3.8 (y = 0.0, 0.1, 0.2, 0.3 and 0.5). Electrochemical methods, specifically, polarization curves have been employed in this study. Copper substitution yielded good overall performance of the alloys.